MEJA KERJA DENGAN ALAT PEMBUAT LUBANG PEN UNTUK MENINGKATKAN KUALITAS DAN KECEPATAN PEMBUATAN PINTU KAYU - Nurhadiyanto, Didik; Rachmad, Suprapto (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2004)
In making  wood  crafting   specially   making  of door  and  shutter  leaf oftentimesobtained    a handicapped    door  product  at shares  pen  hole  in the  form  of   barst  / break, the  difficulty    make   the  door   leaf  if  market   request   quite   a  lot,  and  narrow   tightworkplace   so that needed  a workbench   which  inuliti  function  so that  all workable   doormaking  work  the  desk.  Considering    problems   faced  by this  wood  industry  hence  the industry   require   to  be  assisted   by given  a appliance   of  door  maker   in the  form  of  a workbench   of multi  function   provided   by the  appliance   of hole  pen  maker.   With  the workbench    all  worker   can   finish   the  work   of  door   making   start   from   cutting   of'workpiece.making    'of hole  pen  come  up with  the setting.  The  aim of this  program   is to" perform   and  make  the  workbench   by means  of hole  pen  to  increase  quality  and  time efficiency,   so that  small  industry  can  do the  mote order.In   executing    this   program    we   take   the   following    stages    :  (1)  planningI workbench   to  produce   the  leaf  of door  or  window,   matching   with  society  condition. So  that   this   appliance    easy   to  accepted    by  society   hence   this   appliance    own   the following   specification:     Easy  to operate   it, economize   the  place,  work  of making   of, door   leaf   become   easier,   (2)  testing   workbench    to  make   door   in  wood   industry industry  "UD. W ARSIDI"   to know  until  where  the  appliance   perforrnace,    covering   ist amenity   and  speed   finish   the  making   of  door   leaf.  (3)  door  leaf  yielded   from  this appliance compared    to  by  its  quality   with  the  door  leaf  made  conventionally.     (4  ) machine   completiori   its performance    according   to  plan  (5) delivering   the  machine   at partner  industry  to be utilized  so that  can  be productive.   (6) compiling   final  report  of activity  execution,   Result  of inferential   workbench   perfomance   test-drive   as follows: (1) Maker  of hole  pen of this  desk  can function   better.  Hole  diameter   chisel  between   9 up to  IS  rnm.  (2)  Compered   to  workmanship    in conventionally    making   of  hole  pen with  this  desk   is  quicker   till  4  times.(3)    desk  can  be  used  better   to  reap  the  side goodness   step  aside  and  also  wide  side.(4)   long desk  of the  size  2.03  rn, wide  0,84  rn, high  0,7Im,    speed   turn  around   the  motor   is 2.800  rpm,   speed  turn  around   to  drill, 2.800  rpm,  (5) with.this   workbench,   during  2 day  can  make  8 shutter  and  2 door  leaf, whereas   without  using  workbench   only  can  make  5 shutter  and  1 door  leaft (6) quality of  result   of  work   in making   softer   hole  pen  when  compared   to  a  manual   work  (7) efficiency   of place  use very  high.'Key word:   workbench,   hole pen, door,  and window